ANALISIS PEMBERIAN INSENTIF PAJAK PENGHASILAN PELAKU USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) TERDAMPAK PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) - Santi Wulandari; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2021)
The COVID-19 pandemic has made a huge impact on people's social life in all sectors. Social distancing policies have brought about a big change in people's lifestyles. Deteriorating economic conditions due to the pandemic have made it difficult for people, especially business actors, to make sales, fulfill obligations or pay debts, and have difficulty paying taxes. Taxes have a function as a tool to regulate society in the economic, social, and political fields to reach a certain goal. The government has implemented a package of economic policies such as fiscal, monetary, and financial services regulation as a measure to reduce the impact of the COVID-19 pandemic. The provision of income tax incentives is one of the fiscal policies provided by the government to Micro, Small, and Medium Enterprises (MSME) actors is expected to cope with the impact of COVID-19. The provision of tax incentives to business actors is expected to create a multiplier effect so that public welfare is guaranteed. Therefore, the writing of this thesis will focus on the regulations of income tax incentives for MSME actors and their urgency in the national economic recovery.